Relationship Among the Physico-Chemical Parameters of Soil and Water in Different Wetland Ecosystems - Panda, Bibhu Prasad; Barik, Manas; Mahapatra, Biswajita; Parida, Siba Prasad; Dash, Aditya Kishore; Pradhan, Abanti (Asian Journal of Chemistry, 2020)
The quality of life in water bodies depends on their physico-chemical properties and biodiversity. These physico-chemical properties are being disturbed by continuous addition of industrial, municipal and agricultural wastes which make them unfit for different organisms. This study describes the physico-chemical factors in soil and water of all sampled wetlands and the relationship among them in wetland ecosystem. All these analysis were done by using analytical techniques as described by standard methods for examination of water and wastewater. Physico-chemical parameters of water and soil also interlinked and correlated among each other. Sometimes these parameters work as a cycle to maintain the equilibrium in the ecosystem. Higher level of research work is needed to control the source of pollution to wetlands. By controlling the physico-chemical parameters of habitat, the diversity, density and richness of various wetland dependent species can be controlled in wetland ecosystem.